Warlord - Keith Quincy (Hmong Studies Journal, 2000)
This is Chapter Eight (Warlord) of Harvesting Pa Chay's Wheat: The Hmong and America's Secret War in Laos, scheduled for publication in March 2000. The chapter chronicles the events that led to Vang Pao's rise to commander, and warlord, of the second military region. It also describes the political machine he created, a vast system of patronage and graft designed to co-opt clan notables (many of them potential political rivals) and, if this failed, a program of assassination for trouble-makers. Vang Pao also acquired wives from various clans to forge ties to clan leaders. To induce ordinary Hmong to support the war effort he spawned, with CIA money and sponsorship, a massive system of welfare that would eventually make more than a hundred thousand Hmong dependent on him for their survival.